Modeling the Optimal Supply Chain of Liquefied Natural Gas as Fuel in Fishing Vessels in Mexico - Hernández-Palomo, Giovanna; Rodríguez Aguilar, Román; Venegas-Martínez, Francisco (My University, 2022)
The global energy transition process has generated a set of modifications in the generation and consumption of energy. Environmental objectives have gained great relevance for regions, countries and companies. The fishing sector has been identified as having a broad environmental impact, which is why the transition to cleaner energy sources in this sector has been considered. One of the proposed strategies is based on the transition from the diesel engines of the ships to the use of liquefied natural gas (LNG), however, this transition requires guaranteeing the supply of fuel as well as the process of reconversion of units in operation and the impulse of LNG gas engines for new units. This work presents a proposal for the design of an LNG gas supply chain for the fishing industry in the State of Tampico in Mexico that allows evaluating the feasibility of the transition from the use of diesel to natural gas in fishing vessels. The main results show the feasibility of the transition in the fuel supply and economic and environmental benefits for the fishing industry. However, there is a significant challenge in converting units in operation to the use of natural gas due to the lack of public policies that promote and support its use in this sector. © Mobile Networks and Applications
Keywords: Supply chain; Liquefed natural gas; Fishing vessels; Monte Carlo simulation; Optimization models